2014
DOI: 10.3329/cmoshmcj.v13i3.21020
|View full text |Cite
|
Sign up to set email alerts
|

Complimentary Feeding Practices in Under-2 Children

Abstract: Background: Complimentary feeding (CF) practices are quiet frustating in our country. Innaproprite foods in first two years of life have detrimental impact on health and growth of children. The aim of the study was to see the present pattern of CF practices, to identify wrong practices and to develop awareness among medical professionals so that they may encourage appropriate practices more vigorously for reducing child mortality and morbidity. Methods: A cross-sectional study was conducted from October, 2011 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 15 publications
2
18
0
3
Order By: Relevance
“…H) found that 59.0% of 6-11 month olds, and 59.8% of 12-24 month olds, were fed at the recommended frequency for breastfed children [14]. This was similar to Paul (WOE = M) who found that frequency was appropriate in 53.5% [35]. In Saleh et al (WOE = M), frequency rates varied by age and exclusive breastfeeding status; they found that 33% of non-exclusively breastfed 6-8 month olds were fed 3 times per day, compared to 81% of exclusively breastfed 12-23 month olds [40].…”
Section: Iron Rich Foodssupporting
confidence: 67%
See 4 more Smart Citations
“…H) found that 59.0% of 6-11 month olds, and 59.8% of 12-24 month olds, were fed at the recommended frequency for breastfed children [14]. This was similar to Paul (WOE = M) who found that frequency was appropriate in 53.5% [35]. In Saleh et al (WOE = M), frequency rates varied by age and exclusive breastfeeding status; they found that 33% of non-exclusively breastfed 6-8 month olds were fed 3 times per day, compared to 81% of exclusively breastfed 12-23 month olds [40].…”
Section: Iron Rich Foodssupporting
confidence: 67%
“…The most commonly mentioned source of feeding advice was healthcare professionals, including doctors and hospital staff (5 studies [14,17,20,35,43]). The next most common source was from family members (4 studies [14,20,26,35]).…”
Section: Sources Of Advice For Feedingmentioning
confidence: 99%
See 3 more Smart Citations